PERADILAN PEREMPUAN: KEBIJAKAN KRIMINAL TERINTEGRASI DALAM MELINDUNGI PEREMPUAN - Maghfiroh (Al'Adalah, 2013)
The number of domestic violence cases increasing each year, as reflected in the Annual Report of the National Commission for Women, 2010. However, the actual number is not represent the reality. The people tend to be reluctant to report their cases because fear for bear the shame, stigmatization from society, "blindness" of law, the judicial process is long and laborious due to the absence of a special court for cases of domestic violence. In addition, the court, either public or religious, seems also less responsive in handling cases of domestic violence, including the lack of holding the principle of neutrality.